Global Prevalence of Yersinia enterocolitica in Cases of Gastroenteritis: A Systematic Review and Meta-Analysis - Seyed Mohammad Riahi; Ehsan Ahmadi; Tayebeh Zeinali (International Journal of Microbiology)
The prevalence of Yersinia enterocolitica in gastroenteritis is often underestimated. It relates considerably to morbidity and medical expenses around the world. Understanding the cause of gastroenteritis leads to making the appropriate treatment decisions. We systematically searched PubMed, Science Direct, Embase, and Scopus to identify all published studies between Jan. 1, 2000, and Dec. 31, 2019, to assess the prevalence of Y. enterocolitica in gastroenteritis patients. A total of 5039 articles were identified that lead to the extraction of data from 47 of them. The pooled prevalence of Y. enterocolitica in cases of gastroenteritis was estimated as 1.97% (1.32–2.74%) in the culture method and 2.41% (1.07–4.22%) in the molecular method. Among the biotypes of Y. enterocolitica, 1A (62.48%) and 1B (2.14%) had the most and least prevalence, respectively. Serotype O3 Y. enterocolitica with 39.46% had the highest and O5,27 with 0.0% had the least prevalence in gastroenteritis cases. In conclusion, the findings of this systematic review show that Y. enterocolitica is prevalent in gastroenteritis in all age groups. Serotypes O3 and O9 of Y. enterocolitica had the highest prevalence and O5,27 had the least prevalence in diarrheal patients. The prevalence of Y. enterocolitica was similar in both gender and different seasons. It should be noted that to determine the role of the organism, more studies are needed especially in food-borne diseases.